FAKTOR-FAKTOR YANG MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS PADA PESERTA DIDIK SELAMA PANDEMI COVID-19 - agraprana, putu rama; Nurcahyo, Firmanto Adi (Peneliti.net, 2024)
Pandemic COVID-19 is an outbreak of the condition of the spread of the corona virus (COVID-19) throughout the world. This requires many countries, one of which is Indonesia, to carry out high-scale social restrictions according to the rules of the central government. This condition has an impact on the world of education where previously teaching and learning activities were always carried out offline (face to face) but now must be done online (online). The COVID-19 pandemic has caused students to experience emotional separation from their immediate environment such as family, friends, decreased performance, study period, and experienced pressure due to quarantine. Psychological well-being is needed in order to create a maximum and comfortable learning process for students. This study aims to explain the factors that can increase the Psychological Well-being of Students during the COVID-19 Pandemic. The literature review was conducted on 10 literatures with varying characteristics and number of respondents. The results of the literature review show that there are 6 types of factors that can improve psychological well-being, namely emotion regulation, gratitude, social support, time management, psychological capital, and coping strategies.